TERMITE RESISTANCE OF SAGO PARTICLE BOARD WITH CITRIC ACID-SUSCROSE ADHESIVE - Nurhaida Nurhaida; Yulanda; Yuliati Indrayani; Dina Setyawati (Jurnal Belantara, 2026)
In general, particle board uses formaldehyde-based synthetic adhesives. One of the ways of minimizing the use of synthetic adhesives is by using natural adhesives such as citric acid and sucrose. Previous studies on particle board particularly regarding the physical and mechanical properties of particle board made of dregs and bark fiber of sago (Metroxylon spp) based on layer composition and citric acid-sucrose ratio, show that in addition to its physical and mechanical properties, the quality of particle board is also determined by its resistance to attacks by wood destroying organisms such as termites (Coptotermes curvignathus). This study used a completely randomized factorial design (CRD) with two factors, namely layer composition (70/30, 60/40, 50/50) and citric acid- sucrose ratio (0/100, 25/75, 75/ 25, 100/0). The research found that the value of weight loss in the sample that was fed to termites at the end of the test was 7.32-13.22%. The highest average weight loss value was found in the particle layer composition of 50/50 and the citric acid to sucrose ratio of 0/100, which was 13.22%. Meanwhile, the lowest average weight loss value was found in particleboard with the particle layer composition of 70/30 and the citric acid to sucrose ratio of 100/0, which was 7,3207%. The highest percentage of termite mortality, which reached 100%, was found in particle board with the particle layer composition of 70/30 with the citric acid to sucrose ratio of 100/0. Meanwhile, the lowest percentage of termite mortality was 89.81% in a 50/50 layer composition with a 0/100 citric acid to sucrose ratio. Particle board made of sago fiber and bark with a layer composition of 70/30 and a ratio of citric acid to sucrose of 100/0, classified under class 2 durability, is the optimum treatment to resist termite attack.